Training Data Analysis To Increase The Capacity Alumni - Romadlona, Nohan Arum; Tama, Tika Dwi; Deniati, Ema Novita; Pratama, Aditya Yudha; Susanti, Meirina Nur Asih; Ramadhani, Evada Mutiara (Tarqabin Nusantara Group, 2024)
Aftersales is a routine program carried out to increase the capacity of alumni, especially alumni of Public Health Sciences, Universitas Negeri Malang. This training took the theme of data analysis which was carried out six times both online and offline. Training results were measured through pre- and post-test questionnaires for 15 participants. The results show that there is a significant increase in knowledge p value (<0.005). Statistical data analysis is a topic that is expected to be able to increase knowledge, skills and support alumni according to their field of work.